2018
DOI: 10.1111/cge.13132
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and further delineation of the SETD5 phenotype leading to global developmental delay, variable dysmorphic features, and reduced penetrance

Abstract: Diagnostic exome sequencing (DES) has aided delineation of the phenotypic spectrum of rare genetic etiologies of intellectual disability (ID). A SET domain containing 5 gene (SETD5) phenotype of ID and dysmorphic features has been previously described in relation to patients with 3p25.3 deletions and in a few individuals with de novo sequence alterations. Herein, we present additional patients with pathogenic SETD5 sequence alterations. The majority of patients in this cohort and previously reported have devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…The reported mutation expanded the phenotypic spectrum of mutations previously found in the SETD5 gene, allowing the inclusion of the early‐onset epileptic encephalopathies (EOEEs) as a novel condition associated with SETD5 mutations (Kobayashi et al, ). This same insertion was found as a de novo event in other three patients: two males and one female (Powis et al, ). In the first male patient, with 3 years old, the variant was associated with developmental delay and dysmorphic features.…”
Section: Genetic Variants Of Setd5supporting
confidence: 71%
See 3 more Smart Citations
“…The reported mutation expanded the phenotypic spectrum of mutations previously found in the SETD5 gene, allowing the inclusion of the early‐onset epileptic encephalopathies (EOEEs) as a novel condition associated with SETD5 mutations (Kobayashi et al, ). This same insertion was found as a de novo event in other three patients: two males and one female (Powis et al, ). In the first male patient, with 3 years old, the variant was associated with developmental delay and dysmorphic features.…”
Section: Genetic Variants Of Setd5supporting
confidence: 71%
“…Among the LoF SNVs in SETD5 , four correspond to nonsenses variants as follows (all genomic coordinates are based on human reference genome, build Hg19): NM_001080517:c.1195A > T (p.Lys399*), NM_001080517:c.1333C > T (p.Arg445*), NM_001080517:c.1866C > G (p.Tyr622*) and NM_001080517:c.3001C > T (p.Arg1001*). The mutation c.3001C > T, was also reported in a male with ten years old with developmental disability and dysmorphic features (Powis et al, ). In the same study, in patients with developmental delay, behavioral/psychiatric issues, it was found the following likely LoF SETD5 de novo variants in SETD5 : NM_001080517:c.1655_1656insA, NM_001080517:c.1783‐2A > T, NM_001080517:c.582dupA (p.Ala195Serfs*), NM_001080517:c.1967delT (p.Leu656*) and NM_001080517:c.3246delT (p.Ala1083Leufs*61).…”
Section: Genetic Variants Of Setd5mentioning
confidence: 77%
See 2 more Smart Citations
“…The SET domain containing protein 5 ( SETD5 ) gene (MIM 615743) encoding a conserved methyltransferase expressed throughout the brain was already known to be the crucial determinant of the 3p25.3 deletion syndrome associated with ID, language delay and dysmorphic features (MR23, MIM 615761) . Recently, SETD5 loss‐of‐function mutations have been disclosed by diagnostic exome in a consistent cohort of patients expressing a highly variable phenotype, like the first reported familial syndromic ID cases . Interestingly, SETD5 mutations have been found in patients with suspected CdLS or KBG (Finelli, personal communication) (Table S3).…”
Section: Dd/id Syndromes Caused By Defects In Epigenetic Regulatorsmentioning
confidence: 99%